2008
DOI: 10.1111/j.1349-7006.2008.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Gli1contributes to the invasiveness of pancreatic cancer through matrix metalloproteinase‐9 activation

Abstract: The hedgehog (Hh) signaling pathway has been reported to be associated with the growth of pancreatic cancer, but its role in the invasive phenotype is poorly understood. Therefore, we investigated the role of the Hh pathway in pancreatic cancer cell invasiveness using a Matrigel invasion assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 27 publications
7
56
0
Order By: Relevance
“…Furthermore, it was identified that the mRNA and protein levels of Gli1, TGF-β1 and CXCR4 were coordinately downregulated in the cyclopamine-treated AGS cells, and that the quantity of TGF-β1 secreted into the culture supernatant was significantly reduced following a 24-h treatment with 5 and 10 µM cyclopamine. These findings are in agreement with a number of previously conducted studies (25,36,37). To further elucidate the role of Hh as an important regulator in AGS cells, the present study demonstrated that the Hh signaling pathway appears to regulate tumor invasion and metastasis via TGF-β1 and CXCR4.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, it was identified that the mRNA and protein levels of Gli1, TGF-β1 and CXCR4 were coordinately downregulated in the cyclopamine-treated AGS cells, and that the quantity of TGF-β1 secreted into the culture supernatant was significantly reduced following a 24-h treatment with 5 and 10 µM cyclopamine. These findings are in agreement with a number of previously conducted studies (25,36,37). To further elucidate the role of Hh as an important regulator in AGS cells, the present study demonstrated that the Hh signaling pathway appears to regulate tumor invasion and metastasis via TGF-β1 and CXCR4.…”
Section: Discussionsupporting
confidence: 82%
“…The Hh signaling pathway was initially recognized for its role in modulating embryonic cell proliferation and differentiation (1-4); however, more recently, it has been demonstrated that Hh is important in the proliferation of various types of cancer cells, including lung, pancreatic and gastric cancer cells (12,14,16,(24)(25)(26). While the mechanisms of the Hh signaling pathway in promoting gastric tumorigenesis and regulating downstream target genes are largely unknown, various lines of evidence indicate that a number of key factors, such as TGF-β1 and CXCR4, are actively involved.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been confirmed that the Hh pathway participates in cell migration and angiogenesis processes and is correlated with the severity of the associated tumor (27)(28)(29), additionally, disruption of Hh pathway has been shown to inhibit metastasis in pancreatic cancer and gastric cancer (29)(30)(31), the relationship between the Hh signaling pathway and aggressiveness of HCC cells remains unclear. It is necessary to investigate whether the signaling influences proliferative and invasive potential of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, matrix metalloproteinase-9 (MMP-9) and ER were shown to increase invasiveness through activation of the Hh pathway. (50,52) Nagai et al (52) showed that Gli1 contributes to the invasiveness of pancreatic cancer. Moreover, we reported that Hh signaling contributes to invasiveness under hypoxic conditions, which is observed in regions that are distant from the supporting tumor vasculature and is characteristic of pancreatic cancer.…”
Section: Contribution Of the Hh Signaling Pathway To Cancer Progressimentioning
confidence: 99%